Job satisfaction among bank employees of San Jose, Antique - Feranil, Ma. Concepcion Alvaniz
Increasing the employees' level of satisfaction at work is becoming one of the most pressing problems that must be dealt with in every organization today. As such, the researcher's desire to contribute to this cause, prompted her to undertake this particular study. In this light, this study has the following objectives: a) To describe the level of satisfaction at work of bank employees in relation to the different job factors when they are classified according to gender and job level; b) To describe the general level of satisfaction of the respondents when they are classified according to gender and job level; and c) To determine whether there are differences in the level of satisfaction of bank employees when they are classified according to gender and job level. The focus of the study is limited to the above mentioned objectives. , The study was conducted in the Municipality of San Jose, Antique. The respondents were branch employees of the five banking institutions namely: Philippine National Bank, Development bank of the Phils., Land Bank of the Phils., Philippine Commercial International Bank and Allied Bank Inc.. Statistical computations used in the study include the Mann Whitney U test, averages and percentages. Mann Whitney U test was used to determine whether differences in employees level of satisfaction at work is dependent on their gender and job level. The employees level of satisfaction at work was analyzed by the use of a four point scale wherein point values 4, 3, 2, and 1 were assigned to categories of completely satisfied, moderately satisfied, slightly satisfied and not satisfied respectively. The higher the score, the higher one's level of satisfaction is., Result of the study showed that employees level of satisfaction in relation to the eight job factors mentioned above when classified according to gender is one which falls under somewhat satisfied response. When tested using the Mann Whitney U Test, it was found that there were no differences in their level of satisfaction except on the job factors identified as working conditions and nature of work. employees level of satisfaction in relation to the eight job factors mentioned above when they were classified according to job level is one which falls under the somewhat satisfied response except on job factors namely: security and nature of work where they obtained an average score which fell under the very satisfied response category. Result of the Mann Whitney U test showed that there were differences in their level of satisfaction when classified according to job level except on job factor identified as compensation. With regards to employees general or over-all level of satisfaction at work, result shows that when classified according to gender and job level, their level of satisfaction fell under the somewhat satisfied response category. When tested using the Mann Whitney U test, computations showed that there were differences in their level of satisfaction at work when they were classified according to gender and job level.